A Critical Discourse Analysis Of Selected Articles In Malaysia’s Official Gst Website - Ong, Cheng Teik (2022)
The main objective of the study is to examine the linguistic manifestations of these discourses and their underlying ideological underpinning predicated on Fairclough’s concepts of interdiscursivity, members’ resources, ideology, and his framework consisting of experiential values of words, as well as van Dijk’s ideology of us versus them and his ideological square of inclusion and exclusion.